Assessing psychosocial elements of crowds during hajj: scale construction and content validation - Shuib, Mohd Arif; Abdul Rahman, Shukran; Mohd Mahudin, Nor Diana (2013)
Effective and safe management of large crowds during Hajj are vital as the statistics of pilgrims or hujjaj are reaching four million per season in the coming years. Capturing the underlying psychological and social factors affecting this crowd type before the Hajj season could yield efficient safety practices, evacuation simulations, and injury preventions. The current study aims at addressing the gap in the literature in terms of assessing psychosocial elements of crowds during Hajj. A new measuring instrument, which includes 104 self-rating questions divided into three sub-scales, is proposed. Using a pool of items accumulated from the statements of pilgrims during an Umrah season, the preliminary internal reliability of the scale will be established. Content validity ratio will be calculated by a group of subject matter experts and used to demonstrate the instrument's content validity. A series of item analysis and item revision procedures will also be conducted to increase the instrument’s psychometric properties. It is hoped that the development of this scale will offer important insight on effective and safe simulation of crowds during Hajj. Some possible implications of this new instrument are discussed in relation to test administrations, crowd dynamics, and overall Hajj management.